IL-1β promotes IL-9-producing Th cell differentiation in IL-2-limiting conditions through the inhibition of BCL6 - Canaria, D. Alejandro; Clare, Maia G.; Yan, Bingyu; Campbell, Charlotte B.; Ismaio, Zachariah A.; Anderson, Nicole L.; Park, Sungtae; Dent, Alexander L.; Kazemian, Majid; Olson, Matthew R. (Frontiers in Immunology, 2022)
IL-9-producing CD4+ T helper cells, termed Th9 cells, differentiate from naïve precursor cells in response to a combination of cytokine and cell surface receptor signals that are elevated in inflamed tissues. After differentiation, Th9 cells accumulate in these tissues where they exacerbate allergic and intestinal disease or enhance anti-parasite and anti-tumor immunity. Previous work indicates that the differentiation of Th9 cells requires the inflammatory cytokines IL-4 and TGF-b and is also dependent of the T cell growth factor IL-2. While the roles of IL-4 and TGF-b-mediated signaling are relatively well understood, how IL-2 signaling contributes to Th9 cell differentiation outside of directly inducing the Il9 locus remains less clear. We show here that murine Th9 cells that differentiate in IL-2-limiting conditions exhibit reduced IL-9 production, diminished NF-kB activation and a reduced NF-kB-associated transcriptional signature, suggesting that IL-2 signaling is required for optimal NF-kB activation in Th9 cells. Interestingly, both IL-9 production and the NF-kB transcriptional signature could be rescued by addition of the NF-kB-activating cytokine IL-1b to IL-2-limiting cultures. IL-1b was unique among NF-kB-activating factors in its ability to rescue Th9 differentiation as IL-2 deprived Th9 cells selectively induced IL-1R expression and IL-1b/IL-1R1 signaling enhanced the sensitivity of Th9 cells to limiting amounts of IL-2 by suppressing expression of the Th9 inhibitory factor BCL6. These data shed new light on the intertwined nature of IL-2 and NF-kB signaling pathways in differentiating Th cells and elucidate the potential mechanisms that promote Th9 inflammatory function in IL-2-limiting conditions.